2020
DOI: 10.3390/jcm9082452
|View full text |Cite
|
Sign up to set email alerts
|

Insight in miRNome of Long-Term Non-Progressors and Elite Controllers Exposes Potential RNAi Role in Restraining HIV-1 Infection

Abstract: Long-term non-progressors (LTNP) and elite controllers (EC) represent spontaneous natural models of efficient HIV-1 response in the absence of treatment. The main purposes of this work are to describe the miRNome of HIV-1 infected patients with different extreme phenotypes and identify potentially altered pathways regulated by differentially expressed (DE) miRNAs. The miRNomes from peripheral blood mononuclear cells (PBMCs) of dual phenotype EC-LTNP or LTNP with detectable viremia and HIV-infected patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Several studies have shown that PBMCs from ECs have a miRNA repertoire that is distinct from that of HIV-1 ART-naïve progressors, and such a difference may in part explain the control of viral infection in ECs ( Witwer et al., 2012 ; Reynoso et al., 2014 ; Ayala-Suárez et al., 2020 ). In this context, we assessed the levels of miRNA-103 and CCR5 mRNA in CD4 + T cells from ECs and ART-naïve progressors and found that CCR5 mRNA in CD4 + T cells obtained from ECs was significantly decreased when compared to that in CD4 + T cells from ART-naïve progressors, in line with recently published results ( Claireaux et al., 2022 ; Gonzalo-Gil et al., 2019 ; Meijerink et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that PBMCs from ECs have a miRNA repertoire that is distinct from that of HIV-1 ART-naïve progressors, and such a difference may in part explain the control of viral infection in ECs ( Witwer et al., 2012 ; Reynoso et al., 2014 ; Ayala-Suárez et al., 2020 ). In this context, we assessed the levels of miRNA-103 and CCR5 mRNA in CD4 + T cells from ECs and ART-naïve progressors and found that CCR5 mRNA in CD4 + T cells obtained from ECs was significantly decreased when compared to that in CD4 + T cells from ART-naïve progressors, in line with recently published results ( Claireaux et al., 2022 ; Gonzalo-Gil et al., 2019 ; Meijerink et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses of genetic studies showed a genome-wide significant association between the CCR5 locus and viral load, highlighting the impact of CCR5 expression limitation on HIV-1 replication and control ( McLaren et al., 2015 ). Indeed, it has been shown that PBMCs from ART-naïve progressors may have less total miRNAs than cells from ECs ( Ayala-Suárez et al., 2020 ). As well, viral infection can have an impact on miRNA expression ( Bennasser et al., 2005 ; Triboulet et al., 2007 ) as viral proteins such as Tat and Vpr have been reported to act as RNA silencing suppressors ( Casey Klockow et al., 2013 ; Cojo et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting strategy consists of restoring the killing capacity of cells by miRNA modulation. Therefore, the involvement of miRNAs in CD8 + T cells cytotoxicity has also been investigated (29)(30)(31)(32)(33)(34)(35). However, to our knowledge, no attempts have been made to restore the killing capacity of cells by miRNA modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is debated that whether host RNA interference (RNAi) contributes to immune responses against HIV-1. Nevertheless, several miRNAs are differentially regulated in HIV-1 elite controllers as compared to typical progressor patients, suggesting that HIV-1 interferes with host RNAi ( 95 ). HIV-1 manipulates host RNAi mechanisms through its RNA elements such as RRE (Rev Response Element) and TAR (Trans Activation Response) as well as Rev and Tat proteins.…”
Section: Discussionmentioning
confidence: 99%